Air quality in swimming pool facilities in consideration of the occurrence of volatile DBPs - Żak, Magdalena; Melaniuk-Wolny, Edyta (Instal, 2023)
Numerous by-products of water disinfection (DBPs) are identified in pool waters. Some of them, due to their high volatility (trihalomethanes, chloramines), are transferred from water to air and, with their widely reported harmfulness, can pose serious health risks associated with inhalation exposure to these compounds for people staying in pool facilities. The existing risk will be largely determined by the concentration of these compounds in the air, the duration of exposure and the activity of people. Concentrations will be determined by numerous factors of facility use, including the ventilation system used. Due to numerous reports of poor air quality in many facilities, this article conducts a broad review of the literature on the occurring levels of volatile DBPs (trihalomethanes and chloramines) concentrations in the air above swimming pools and in other rooms within swimming pool facilities. The legal status of the requirements for conducting measurements of volatile DBB and standards for the concentration of trihalomethanes and chloramines in the air was also presented. The importance of ventilation and the solutions used in this type of area affecting the air quality was also described.